Immunogenicity and efficacy of infectious bursal disease virus (IBDV) vaccines against the Malaysian variant IBDV in broiler chickens - Paniz, Zarghami Dastjerdi (2024)
Infectious bursal disease (IBD) (Gumboro disease) is a viral disease in young chickens that causes immunosuppression. It is caused by the infectious bursal disease virus (IBDV), a highly resistant non-enveloped RNA virus. Effective disease control and prevention strategies focus on farm biosecurity and vaccination. However, the emergence of novel variant IBDV (nvarIBDV) has challenged vaccine efficacy. An improved version of the herpesvirus of turkey (HVT) vector vaccine, HVT+IBD+ND, has been developed recently. However, the efficacy of IBDV vaccines has not been evaluated against the emerging Malaysian variant of IBDV in commercial broiler chickens. This study evaluated the immunogenicity and efficacy of live attenuated and viral vector vaccines against variant IBDV in chickens. In the immunogenicity study, ELISA method was used to detect antibody titers. The HVT+IBD group had a higher mean antibody titer compared to the HVT+IBD+ND group, as detected by the VP2 IBDV-specific ELISA (p<0.05) in the broiler chickens at 28 days old. Both vaccinated groups showed low bursal lesion scores. As expected, antibody titers were detectable by the VP2 IBDVspecific ELISA but not with the whole IBDV-specific ELISA. Real-time qPCR showed a significantly higher HVT load in the HVT+IBD group (p<0.05). Upon comparison with the IBD-BLEN, it seems that the IBD-BLEN vaccine generates a high mean antibody titer (1623.00 ± 2031.13 and 4775.00 ± 3418.77) as detected by whole IBDV and VP2 IBDV-specific ELISA, respectively, however, it is associated with a high bursal lesion score of 3.0 at 28-day-old chickens. The efficacy of the HVT-based vaccine against the nvarIBDV strain UPM1432/2019 was evaluated. The HVT+IBD vaccine and HVT+IBD+ND vaccinated birds have seroconversion rates against IBD of 97% and 32.5%, respectively. However, both groups had bursal lesions following challenged with nvarIBDV. The HVT+IBD group had a higher mean antibody titer (7168 ± 3753.26), and less bursal damage at day 7 and 14 post-challenge compared to HVT+IBD+ND (1209.1 ± 1252.88) (p<0.05), indicating the HVT+IBD vaccine offers partial protection against nvarIBDV challenge. In addition, the HVT+IBD group had a statistically higher normalized HVT value in the bursa and spleen than the HVT+IBD+ND group (p<0.05). Although the HVT loads were higher for HVT+IBD (p<0.05), variant IBDV loads were similar between groups post-challenge (p > 0.05), indicating the vaccines could not induce virus clearance. The immunosuppression study showed variant IBDV challenge could inhibit the antibody response after Newcastle disease (ND) vaccination in broiler chickens with a significant reduction at day 14 post-challenge (1493.0 ± 746.1) (p < 0.05) but not at day 7 (p > 0.05). In conclusion, the current HVT-based vaccines against IBD cannot provide complete protection against the Malaysian variant IBDV infection in commercial broiler chickens. In addition, infection with variant IBDV can suppress the production of antibodies following ND vaccination. Findings from this study recommend implementing new strategies, including the use of variant IBD vaccine in controlling variant IBDV and its immunosuppression effect in broiler chickens.